Oral Anticoagulant Therapy in Patients Receiving Haemodialysis: Is It Time to Abandon It?. (27th November 2013) - Saracyn, Marek; Brodowska-Kania, Dorota; Niemczyk, Stanisław
Abstract : Oral anticoagulant (OAC) therapy in haemodialysis patients causes a great deal of controversy. This is because a number of pro- and anticoagulant factors play an important role in end-stage renal failure due to the nature of the disease itself. In these conditions, the pharmacokinetic and pharmacodynamic properties of the OACs used change as well. In the case of the treatment of venous thromboembolism, the only remaining option is OAC treatment according to regimens used for the general population. Prevention of HD vascular access thrombosis with the use of OACs is not very effective and can be dangerous. However, OAC treatment in patients with atrial fibrillation in dialysis population may be associated with an increase in the incidence of stroke and mortality. Doubts should be dispelled by prospective, randomised studies; at the moment, there is no justification for routine use of OACs in the above-mentioned indications. In selected cases of OAC therapy in this group of patients, it is absolutely necessary to control and monitor the applied treatment thoroughly. Indications for the use of OACs in patients with end-stage renal disease, including haemodialysis patients, should be currently limited.